2013
DOI: 10.1093/icvts/ivt051
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant mediastinitis due to extended-spectrum beta-lactamase-producing Klebsiella pneumoniae: atypical presentation and spreading following cardiac surgery

Abstract: Mediastinitis due to Klebsiella pneumoniae, related to thoracic wall contamination after cardiac surgery, has rarely been described. We aim to report a case of fulminant mediastinitis due to extended-spectrum beta-lactamase-producing K. pneumoniae, secondary to a disseminated concomitant pulmonary infection. The patient remained pauci-symptomatic until clinical manifestations of sepsis acutely appeared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition, infection with these microorganisms was associated with a poorer prognosis in subjects with mediastinitis. Charbonneau et al [ 269 ] showed that in-hospital mortality at 30 days was significantly higher in patients with GNB mediastinitis compared to those caused by Gram-positive bacteria (31.9% versus 17.0%; p = 0.004) [ 269 , 271 ].…”
Section: Medical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, infection with these microorganisms was associated with a poorer prognosis in subjects with mediastinitis. Charbonneau et al [ 269 ] showed that in-hospital mortality at 30 days was significantly higher in patients with GNB mediastinitis compared to those caused by Gram-positive bacteria (31.9% versus 17.0%; p = 0.004) [ 269 , 271 ].…”
Section: Medical Managementmentioning
confidence: 99%
“…Although Gram-positive microorganisms are the cause of most cases of post-sternotomy mediastinitis, some authors have reported a prevalence of Gram-negative bacilli (GNB) infection of up to 56.7% ( K. pneumoniae 16.4%) [ 271 ].…”
Section: Medical Managementmentioning
confidence: 99%
“…GNB PSM is associated with a more severe outcome, leading to a decrease in survival. Evidence of increasing multidrug-resistant (MDR) GNB infecting DSWI is a great concern and are likely to increase in number in future years [17,19,20]. The proportion of patients with PSM of fungal cause is below 5%.…”
Section: Key Pointsmentioning
confidence: 99%
“…Of interest that an outbreak of PSM caused by Serratia marcescens because of contamination of the aqueous chlorhexidine solution used to prepare the patients’ skin has been reported [18]. Evidence of increasing multidrug-resistant (MDR) GNB infecting DSWI is a great concern and are likely to increase in number in future years [17,19,20]. The proportion of patients with PSM of fungal cause is below 5%.…”
Section: Microbiological Causementioning
confidence: 99%